2021
DOI: 10.1016/j.jbc.2021.100381
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol activates BK channels by increasing KCNMB1 protein levels in the plasmalemma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 67 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Overall, this lack of effect of MβCD treatment on SK Ca /IK Ca channel function is consistent with previous studies (reviewed in [ 49 ]). As highly expressed in smooth muscle cells [ 50 ], large conductance K Ca (BK Ca ) channels are suppressed [ 51 ] or activated in response to membrane-enriched cholesterol depending on expression of KCNMB1 and trafficking of BK Ca β 1 subunits [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this lack of effect of MβCD treatment on SK Ca /IK Ca channel function is consistent with previous studies (reviewed in [ 49 ]). As highly expressed in smooth muscle cells [ 50 ], large conductance K Ca (BK Ca ) channels are suppressed [ 51 ] or activated in response to membrane-enriched cholesterol depending on expression of KCNMB1 and trafficking of BK Ca β 1 subunits [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, however, cholesterol down-regulates BK channels and its acute depletion using methyl-β-cyclodextrin potentiates channel activity ( Dopico and Bukiya, 2014 ). However, a recent study using native cerebral artery smooth muscle cells revealed that cholesterol enrichment stimulated BK channels, and this effect was driven by increases in cell membrane levels of β 1 subunits ( Bukiya et al, 2021 ). In support to these findings, smooth muscle cells isolated from human coronary atherosclerotic plaque samples exhibited significantly higher channel activity than those obtained from coronary media segments ( Wiecha et al, 1997 ).…”
Section: Pharmacology Of Bk Channelsmentioning
confidence: 99%
“…In research, randomly-methylated-β-cyclodextrin (MβCD) is most widely used due to its highest efficiency among CD derivatives to extract cholesterol from the cell membrane ( Szente and Fenyvesi, 2017 ; Szente et al, 2018 ). It is typically applied at 3–5 mM for 1 h for membrane cholesterol depletion, while MβCD previously complexed with cholesterol potently elevates membrane cholesterol levels ( Zidovetzki and Levitan, 2007 ; Bukiya et al, 2021 ). In clinical practice and in vivo experiments, hydroxypropyl-β-cyclodextrin (HPβCD) is the most commonly employed CD to deplete cholesterol due to its better safety profile compared to MβCD ( Irie and Uekama, 1997 ; Szente et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%